Analysis of Cell Block and Cytology Specimen Preservation from Lung Aspiration Biopsy - Poernomo, Adinda Sandya; Sandhika, Willy; Budipramana, Vicky Sumarki (Jurnal Kedokteran Brawijaya, 2020)
Cytology smear technique is often used in Indonesia because the process is safe, simple, easy, fast, and cost effective. At present, several studies have found that smears with cell block techniques are of better quality than smears with cytology smear techniques. The aim of this study was to analyze whether the cytology smear technique can produce adequate specimens compared to cell block towards results of lung Fine Needle Aspiration Biopsy (FNAB). Lung FNAB specimens were divided into two parts: one part was processed with cytology and the other part with cell block technique. The specimens were observed under a microscope to count the number of inflammatory cells and the number of artifacts. The numbers of inflammatory cells and artifacts were scored 0-3. The inflammatory cells consisted of neutrophils, lymphocytes and plasma cells, also macrophages. The result showed no significant difference between the number of inflammatory cells in cytology and cell block (p neutrophils=0.543; p lymphocytes and plasma cells=0.192; p macrophages=0.487) in 38 samples. The artifact score comparison test result showed a significant difference between the number of artifacts in cytology and cell block (p=0.027) with more artifacts in cytology. The most common artifact in cytology was air bubble artifacts, while cell block was dominated by torn pieces artifacts. There was no significant difference between the number of inflammatory cells found in cytology and cell block techniques. Cell block technique has less artifacts than cytology, but artifacts found in cytology can be corrected so that the cytology smear technique is still an option.